Depressive Symptom Profiles and Survival in Older Patients with Cancer: Latent Class Analysis of the ELCAPA Cohort Study. (31st December 2018) - Gouraud, Clément; Paillaud, Elena; Martinez‐Tapia, Claudia; Segaux, Lauriane; Reinald, Nicoleta; Laurent, Marie; Corsin, Lola; Hoertel, Nicolas; Gisselbrecht, Mathilde; Mercadier, Elise; Boudou‐Rouquette, Pascaline; Chahwakilian, Anne; et al.
Abstract: Background: The expression of depressive symptoms in older people with cancer is heterogeneous because of specific features of age or cancer comorbidity. We aimed to identify depressive symptom profiles in this population and describe the associated features including survival. Materials and Methods: Patients ≥70 years who were referred to geriatric oncology clinics were prospectively included in the ELCAPA study. In this subanalysis, depressive symptoms were used as indicators in a latent class analysis. Multinomial multivariable logistic regression and Cox models examined the association of each class with baseline characteristics and mortality. Results: For the 847 complete‐case patients included (median age, 79 years; interquartile range, 76–84; women, 47.9%), we identified five depressive symptom classes: "no depression/somatic only" (38.8%), "no depression/pauci‐symptomatic" (26.4%), "severe depression" (20%), "mild depression" (11.8%), and "demoralization" (3%). Compared with the no depression/pauci‐symptomatic class, the no depression/somatic only and severe depression classes were characterized by more frequent comorbidities with poorer functional status and higher levels of inflammation. "Severe" and "mild" depression classes also featured poorer nutritional status, more medications, and more frequent falls. Severe depression was associated with poor social support, inpatient status, and increased risk of mortality at 1 year (adjusted hazard ratio, 1.62, 95% confidence interval, 1.06–2.48) and 3 years (adjusted hazard ratio, 1.49; 95% confidence interval, 1.06–2.10). Conclusion: A data‐driven approach based on depressive symptoms identified five different depressive symptom profiles, including demoralization, in older patients with cancer. Severe depression was independently and substantially associated with poor survival. Abstract : The expression of depressive symptoms in older patients with cancer is complex, with greater heterogeneity than in younger patients. This article identifies different homogeneous classes of depressive symptoms that can assist in analyzing outcomes to avoid inconsistent interpretation of study results.